Mengapa Perusahaan Terlambat Menerbitkan Laporan Keuangan? - Winda Felicia; David Adechandra Ashedica Pesudo (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
Purpose of this research is to assess whether there is a difference between financial statements audit with on time and late publication date. it can be seen through the size pf the company, profit/loss operation, KAP reputation, solvability and profitability of mining public company which are recorded from 2014 until 2016 in Indonesia Stock Exchange. Total sample of this study is 102 using purposive sampling.The data is analyzed by non-parametic test. Results showed that there is a difference on the company’s size, profit/loss operation and KAP reputation, but there is no difference on the solvability and profitability between company that published their financial statements on time and late.